The Post-Racial Mystique : Media and Race in the Twenty-First Century - Squires, Catherine R., 1972- (Book collections on Project MUSE., 2014)
"Despite claims from pundits and politicians that we now live in a post-racial America, people seem to keep finding ways to talk about race--from celebrations of the inauguration of the first Black president to resurgent debates about police profiling, race and racism remain salient features of our world. When faced with fervent anti-immigration sentiments, record incarceration rates of Blacks and Latinos, and deepening socio-economic disparities, a new question has erupted in the last decade: What does being post-racial mean?The Post-Racial Mystique explores how a variety of media--the news, network television, and online, independent media--debate, define and deploy the term "post-racial" in their representations of American politics and society. Using examples from both mainstream and niche media--from prime-time television series to specialty Christian media and audience interactions on social media--Catherine Squires draws upon a variety of disciplines including communication studies, sociology, political science, and cultural studies in order to understand emergent strategies for framing post-racial America. She reveals the ways in which media texts cast U.S. history, re-imagine interpersonal relationships, employ statistics, and inventively redeploy other identity categories in a quest to formulate different ways of responding to race"--